Progress in functional analysis : proceedings of the International Functional Analysis Meeting on the occasion of the 60th birthday of professor M. Valdivia, Peniscola, Spain, 22-27 October 1990 - Valdivia, Manuel, 1928-; Bierstedt, Klaus-Dieter (North-Holland mathematics studies ;, 1992)
This volume includes a collection of research articles in Functional Analysis, celebrating the occasion of Manuel Valdivia's sixtieth birthday. The papers included in the volume are based on the main lectures presented during the international functional analysis meeting held in Pescola (Valencia, Spain) in October 1990. During his career, Valdivia has made contributions to a wide variety of areas of Functional Analysis and his work has had a profound impact. A thorough appreciation of Valdivia's work is presented in J. Horvth's article. In honor of Valdivia's achievements, this volume presents more than twenty-five papers on topics related to his research (Banach spaces, operator ideals, tensor products, Frchet, (DF) and (LF) spaces, distribution theory, infinite holomorphy etc.). While the majority of papers are research articles, survey articles are also included. The book covers a broad spectrum of interests in today's Functional Analysis and presents new results by leading specialists in the field.